2019
DOI: 10.1016/j.devcel.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Live Tracking of Inter-organ Communication by Endogenous Exosomes In Vivo

Abstract: Highlights d Single endogenous EVs can be live-visualized in the zebrafish embryo with CD63-pHluorin d Syntenin in the YSL regulates exosome release into the blood for further dissemination d YSL exosomes are taken up by macrophages and endothelial cells in the tail of the embryo d Uptake is scavenger receptor-and dynamin-dependent and provides trophic support

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
247
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(267 citation statements)
references
References 69 publications
11
247
0
9
Order By: Relevance
“…Cancer-derived EVs have been shown to promote M2 polarisation of TAMs in some cases, and the expression of pro-inflammatory cytokines in others [252][253][254]. Recently, both a fluorescent probe [255,256] and a transgenic line [257] have been developed that specifically label EVs in zebrafish, making it possible to track their transit in a live in vivo model. For example, one study showed that tumour-derived EVs activated macrophages, resulting in a macrophage-dependent promotion of metastatic outgrowth at distal sites [255].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Cancer-derived EVs have been shown to promote M2 polarisation of TAMs in some cases, and the expression of pro-inflammatory cytokines in others [252][253][254]. Recently, both a fluorescent probe [255,256] and a transgenic line [257] have been developed that specifically label EVs in zebrafish, making it possible to track their transit in a live in vivo model. For example, one study showed that tumour-derived EVs activated macrophages, resulting in a macrophage-dependent promotion of metastatic outgrowth at distal sites [255].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…We identify many vesicles with high lipids or proteins content floating in central canal, in agreement with previous observations 31 . The presence of dense exosomes is confirmed using fluorescence labeling ( Supplementary Movie S10, Methods ), and electron microscopy with immunogold labeling of exosomes ( Figure 7h, Methods ) 30 . Note that both optical techniques show similar bidirectional flow of endogenous extracellular vesicles in the CC ( Supplementary Movies S10, S11 ).…”
Section: The Connection From Brain Ventricles To Central Canal In Thementioning
confidence: 81%
“…On the next day, embryos were anesthetized with tricaine and embedded in 1.5% low melting point agarose. Live imaging recordings were performed at 28°C using a Nikon TSi spinningwide (Yokagawa CSUW1) microscope 30 . Other embryos were used for ultrathin cryosectioning and immunogold labeling, in which case they were fixed in 2% PFA, 0.2% glutaraldehyde in 0.1M phosphate buffer pH 7.4 at 3 dpf.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations